An Investigation of the Melt Flow Properties of PP/LDPE Blends - Sangswasd, Chavalit (Frontiers in Engineering Innovation Research, 2003)
Blends of the polypropylene with polyethylene have been prepared by using a Brabender twin-screw extruder. The flow properties of the blends were measured with the Davenport capillary rheometer. The dependence of shear stress on shear rate was approximately represented, for all the blends, by the power law equation. The manner of the dependence of blend viscosity on composition varies widely for the system studied. The viscosity of the blends at 200 degree Celsius goes through a minimum, all the viscosity of the blends at 230 degree Celsius go through a maximum. However, the viscosity of the blends, which have the same shear stress at 230 degree Celsius become lower than those of 200°c. It is possible to produce blends with either greater or less melt viscosity than the individual components by adjusting the composition of blending.